Development of a Dominant Negative Competence‐Stimulating Peptide (dnCSP) that Attenuates Streptococcus pneumoniae Infectivity in a Mouse Model of Acute Pneumonia. (23rd October 2018) - Koirala, Bimal; Lin, Jingjun; Lau, Gee W.; Tal‐Gan, Yftah
Abstract: Streptococcus pneumoniae (pneumococcus) is a prevalent human pathogen responsible for a variety of diseases, including pneumonia, bacteremia, sepsis, meningitis and otitis media, with a death toll of >22 000 a year in the United States alone. Pneumococcus uses the competence regulon and its associated signaling peptide, the competence stimulating peptide (CSP), to initiate its attack on the host and establish an infection. In this work, we set out to: 1) develop a pan‐group quorum sensing inhibitor that could effectively interact with both the pneumococcus ComD1 and ComD2 receptors; and 2) evaluate the utility of dominant‐negative CSPs (dnCSPs) in attenuating pneumococcus infectivity. Our results highlight the potential of inhibiting the competence regulon as a therapeutic approach to combat pneumococcus infections. Abstract : I will survive : Pneumococcus uses the competence regulon and its associated signaling peptide, the competence stimulating peptide (CSP), to initiate its attack on the host and establish an infection. Administering a dominant negative CSP two hours post‐infection attenuated S. pneumoniae infectivity and increased survival in a mouse model of acute pneumonia.